The Influence of Net Profit and Operating Cash Flow on Stock Prices: Main Listing Board Company - Jefriyanto, Jefriyanto; Riyanto, Didik (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2024)
This research aims to determine the influence of each independent variable, net profit and operating cash flow, on the stock price. The research uses quantitative research methods with descriptive analysis and verification analysis approaches. a research approach that uses a lot of numbers, starting from collecting data, interpreting the data obtained, and presenting the results. The research object is healthcare companies listed on the Indonesia Stock Exchange 2019 - 2021. This research uses qualitative - secondary data from financial reports on the official website of the Indonesia Stock Exchange. The population in this research was 25 healthcare companies registered on the IDX at the time this research was conducted. The partial result shows that share prices in the net profit t test have an influence but are not significant, and operating cash flow has a significant effect. In the simultaneous test, the influence of net profit and operating cash flow together has an effect on share price.